Modulatory Effects of Huoxiang Zhengqi Oral Liquid on Gut Microbiome Homeostasis Based on Healthy Adults and Antibiotic-Induced Gut Microbial Dysbiosis Mice Model - Gao, Min; Duan, Xinhao; Liu, Xiang-Ru; Luo, Shiyue; Tang, Shixin; Nie, Hao; Yan, Jing; Zou, Zhen; Chen, Chengzhi; Yin, Qi; Qiu, Jingfu (Frontiers in Pharmacology, 2022)
Traditional herbal medicine (THM) is used worldwide for its safety and effectiveness against various diseases. Huoxiang Zhengqi (HXZQ) is an extensively used Chinese THM formula, targeting gastrointestinal disordered gastroenteritis, via regulating the intestinal microbiome/immuno-microenvironment. However, the specific mechanisms remain largely unexplored, besides as a lifestyle drug, its safety on the gut microbiome homeostasis has never been investigated. In this study, the effects of HXZQ on gut microbiome of healthy adults were investigated for the first time, and the antibiotic-induced gut microbiota dysbiosis mice model was applied for verification. Based on healthy adults, our results revealed that HXZQ exhibited mild and positive impacts on the bacterial diversity and the composition of gut microbiome in healthy state. As for an unhealthy state of gut microbiome (with low bacterial diversity and deficient compositions), HXZQ significantly restored the bacterial diversity and recovered the abundance of Bacteroidetes. In antibiotic-induced mice model, HXZQ distinctly revived the deficient gut microbial compositions impaired by antibiotics. At genus level, the abundance responded most strongly and positively to HXZQ were Bifidobacterium in health adults, and Muribaculaceae, Lactobacillus, and Akkermansia in mice. While the abundance of Blautia in healthy adults, Enterococcus and Klebsiella in mice showed inversely associated with HXZQ administration. At last, HXZQ might exhibit anti-inflammatory effect through regulating the concentration of interleukin-6 in plasma, while causing no significant changes on the colon tissue structure in mice. In conclusion, our results elucidate the safety of HXZQ in daily use, further reveal the modulatory effects of HXZQ on gut microbial community structure. These results will provide new insights into the interaction of THM and gut microbiome homeostasis, and clues about the safe use of THM as a lifestyle drug for its further development.